A Copper Metal–Organic Framework as an Efficient and Recyclable Catalyst for the Oxidative Cross‐Dehydrogenative Coupling of Phenols and Formamides. Issue 10 (23rd August 2013) - Phan, Nam T. S.; Nguyen, Tung T.; Vu, Phuong H. L.
Abstract A crystalline porous metal‐organic framework Cu2(BPDC)2(BPY) (BPDC=4, 4′‐biphenyldicarboxylate, BPY=4, 4′‐bipyridine) was synthesized and characterized by several techniques including XRD, SEM, TEM, thermogravimetric analysis, FTIR, atomic absorption spectrophotometry, hydrogen temperature‐programmed reduction, and nitrogen physisorption measurements. The Cu2(BPDC)2(BPY) could be employed as a heterogeneous catalyst for the copper‐catalyzed cross‐dehydrogenative coupling reaction of DMF with 2‐substituted phenols to form organic carbamates through CH activation under oxidative conditions. The Cu2(BPDC)2(BPY) offered higher catalytic activity than common copper salts such as Cu(OAc)2, CuCl, CuCl2, CuI, and Cu(NO3)2 as well as other Cu–MOFs such as Cu3(BTC)2, Cu(BDC), and Cu(BPDC). The Cu2(BPDC)2(BPY) catalyst could be facilely separated from the reaction mixture, could be recovered and reused several times without significant degradation in catalytic activity.